Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s11606-019-05084-6
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Team Meetings—a Venue to Improve Team Engagement and Quality in Resident Continuity Clinic

Abstract: BACKGROUND Suboptimal continuity, complex patients, and poor resident integration into the Patient-Centered Medical Home (PCMH) structure contribute to limited resident satisfaction with resident continuity clinic (RCC). The Society of General Internal Medicine has recognized the need for resident PCMH training and developed PCMH entrustable professional activities. 1 Studies looking at integrating residents into the PCMH more fully to improve the RCC experience have shown mixed results. Hochman et al. impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…It seemed that advising providers on the lowest two ECLS had significant impact on increasing effective care over time. This was an anticipated outcome supported by literature evidence (Dean, 2021; Lyons et al, 2019) that team communication leads to improved outcomes. Finally, NPs were willing to continue focusing on incorporating two lower effective care areas (Table 3) of sleep hygiene and exercise (USPSTF, 2016, VA, 2022) in future appointments.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…It seemed that advising providers on the lowest two ECLS had significant impact on increasing effective care over time. This was an anticipated outcome supported by literature evidence (Dean, 2021; Lyons et al, 2019) that team communication leads to improved outcomes. Finally, NPs were willing to continue focusing on incorporating two lower effective care areas (Table 3) of sleep hygiene and exercise (USPSTF, 2016, VA, 2022) in future appointments.…”
Section: Discussionsupporting
confidence: 57%
“…Nurse practitioners were willing to review and document PHQ-9 scores, review weekly ECLS, and address the lowest scoring items each week. The team's willingness to communicate, attend meetings, discuss difficulties, and refer patient concerns was predicted in recent literature (Dean, 2021;Inness et al, 2022;Lyons et al, 2019) and reflected in improved team engagement scores at project completion.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As such, resident integration into teams can be challenging, although one recent study demonstrated the benefits of multidisciplinary team meetings. 20 Faculty preceptors often also conduct clinical work part-time, making functional teams and management continuity difficult. Many residency practices are hospital-based and provide care to medically and psychosocially complex patients, making team-based care even more critical.…”
Section: Introductionmentioning
confidence: 99%